Inulin accelerates weight loss in obese mice by regulating gut microbiota and serum metabolites - Wu, Zeang; Du, Zhenzhu; Tian, Yuanyuan; Liu, Miao; Zhu, Kailong; Zhao, Yufan; Wang, Haixia (Frontiers in Nutrition, 2022)
Several studies indicated that the gut microbiome might participate in the beneficial effect of inulin on obesity. However, the mechanisms involved were still largely unknown. Sixteen high-fat diets (HFD)-induced obese C57BL/6 mice were converted to a normal diet and then randomized into two groups, OND (obese mice + normal diet) group gavage-fed for ten weeks with normal saline and ONDI (obese mice + normal diet + inulin) group with inulin at 10 g/kg/day. The body weight of HFD-induced obese mice showed different degrees of decrease in both groups. However, the ONDI group lost more weight and returned to normal earlier. Compared to the OND group, inulin supplementation significantly shifted the composition and structure of gut microbiota, such as higher ɑ diversity. The β diversity analysis also confirmed the changes in gut microbiota composition between groups. At the genus level, the abundance of Alistipes was considerably increased, and it was significantly correlated with inulin supplementation (r = 0.72, p = 0.002). Serum metabolite levels were distinctly altered after inulin supplementation, and 143 metabolites were significantly altered in the ONDI group. Among them, indole-3-acrylic acid levels increased more than 500-fold compared to the OND group. It was also strongly positive correlation with Alistipes (r = 0.72, p = 0.002) and inulin supplementation (r = 0.99, p = 9.2e-13) and negatively correlated with obesity (r = -0.72, p = 0.002). In conclusion, inulin supplementation could accelerate body weight loss in obese mice by increasing Alistipes and indole-3-acrylic acid levels.